The Role of Technology Security and Continuous Improvement on M Payment Satisfaction - Nurhaula, Muhammad Nurhaula Huddin (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
Purpose – The purpose of this study is to examine the effect of technological security and continuous improvement on consumer satisfaction and trust in mobile payment payments. Methodology/approach – This researcher used purposive sampling technique by requiring certain criteria. Respondents are those who have used m-payment services in Indonesia. Questionnaires were distributed through online surveys with a total of 250 research respondents. Hypothesis testing was carried out using SEM (Structural Equation Modeling) AMOS 23. Findings – It was found that, technology security has a positive effect on mobile payment satisfaction, continuous improvement has a positive effect on mobile payment satisfaction, and satisfaction has a positive effect on mobile payment trust. Novelty/value – As technology security and continuous improvement has been an important factor in mobile payment satisfaction this research is still very rare in Indonesia.